Quality of life evaluation of children with sleep bruxism - Gavião Maria; Barbosa Taís S; Castelo Paula M (BMC, 2010)
Abstract Background The study of potential factors associated with sleep bruxism (SB) may help in determining the etiology of such parafunction. Thus, this study aimed to evaluate the quality of life (QoL) of children with SB by means of a generic scale, in addition to the association of sociodemographic characteristics and other parafunctional habits. Methods This cross-sectional study included healthy children of both genders, aged 7.18 ± 0.59 years, with (n = 25) and without (n = 69) signs and symptoms of SB. Data were collected in caries-free children from public schools by applying a translated and validated version of the Autoquestionnaire Qualite de Vie Enfant Image (AUQUEI), clinical examination and interview with the parents. The psychometric properties evaluated for the scale referred to internal consistency (ceiling and floor effects, Cronbach's Alpha coefficient, Items Correlation Matrix, and corrected Item-Total Correlation) and the discriminant validity (t-test). By means of logistic regression with stepwise backward elimination, associations were evaluated between SB and age, gender, body mass index, maternal use of alcohol/tobacco/medicine during pregnancy, maternal age at birth, parent's schooling, presence of sucking habit, nail biting, enuresis, number of children, child's order (first born), occurrence of divorce/parent's death, and AUQUEI scores. Results The results of the AUQUEI psychometric analysis showed homogeneity of items and a Cronbach's alpha coefficient of 0.65; no negative correlations between the items were found. The mean AUQUEI scores for children with SB did not differ significantly from those of children without the parafunction. Only the independent variable "maternal age at birth" showed a significant negative association with SB. Conclusions In the studied sample, children with SB presented scores of QoL that were similar to those without the parafunction, and children from the youngest mothers were more likely to present SB.